AUTOMATED CONTROL SYSTEM IN GREENHOUSE WITH NEURAL NETWORK PREDICTIONS OF EXTERNAL DISTURBANCES - Dudnyk, A. (Energy and Automation, 2016)
Efficiency of creation automation control system in a greenhouse with using solar radiation intensity and temperature predictions by neural networks is shown. so-bidi-language:AR-SA’>on the angular speed, technological and energy characteristics of the feed mixer are conducted. The dependences of uneven mixing and specific consumption of electric on voltage are established.